2000
DOI: 10.1073/pnas.97.12.6568
|View full text |Cite
|
Sign up to set email alerts
|

Defense by foot adhesion in a beetle ( Hemisphaerota cyanea )

Abstract: The beetle Hemisphaerota cyanea (Chrysomelidae; Cassidinae) responds to disturbance by activating a tarsal adhesion mechanism by which it secures a hold on the substrate. Its tarsi are oversized and collectively bear some 60,000 adhesive bristles, each with two terminal pads. While walking, the beetle commits but a small fraction of the bristles to contact with the substrate. But when assaulted, it presses its tarsi flatly down, thereby touching ground with all or nearly all of the bristles. Once so adhered, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
201
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(205 citation statements)
references
References 10 publications
(11 reference statements)
1
201
0
Order By: Relevance
“…It is clear that the elasticity of the substrate is relevant to understand some of these phenomena, including the clumping of the flexible bristles of tarsi of insects when tarsal oil is released (Eisner & Aneshansley 2000) or the adhesive failure (stiction) of micro-cantilevers bent by capillary forces at the evaporating menisci (Mastrangelo & Hsu 1993). Although static problems involving the interplay between capillarity, elasticity, and possibly other forces are well studied, there are very few studies of the dynamics of elastocapillarity, which is the subject of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that the elasticity of the substrate is relevant to understand some of these phenomena, including the clumping of the flexible bristles of tarsi of insects when tarsal oil is released (Eisner & Aneshansley 2000) or the adhesive failure (stiction) of micro-cantilevers bent by capillary forces at the evaporating menisci (Mastrangelo & Hsu 1993). Although static problems involving the interplay between capillarity, elasticity, and possibly other forces are well studied, there are very few studies of the dynamics of elastocapillarity, which is the subject of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…These structures were previously studied by scanning and transmission electron microscopy [2,3], and their adhesive forces were measured using force transducers [4]. Beetle adhesive setae are supplemented with a liquid secretion that is responsible for generating capillary forces on various surfaces [5,6]. Earlier studies have demonstrated that beetle pads adhere well to dry substrates [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…If required, some insects can produce impressive forces, exceeding many times their body weight [1][2][3]. However, during locomotion, their feet have to be able to attach and detach rapidly.…”
Section: Introductionmentioning
confidence: 99%